Perbandingan Perlindungan Konsumen antara Warga Negara dan Non-Warga Negara di Indonesia - Kevin Maulana AG; Citra Lestari; Auliya Arifatun A (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Consumer protection is a fundamental aspect in ensuring social justice and legal certainty for all individuals involved in the market, including citizens (WN) and non-citizens (NWN). This study aims to analyze the differences in legal protection for WN and NWN consumers in Indonesia by examining the legal status as well as the practice of its implementation. The research applies a normative juridical approach with descriptive-qualitative analysis based on the Consumer Protection Law, its derivative regulations, and case studies of court decisions related to consumer disputes. The results show that, normatively, Law No. 8 of 1999 concerning Consumer Protection does not differentiate between citizens and non-citizens. However, in practice, there are significant challenges such as administrative barriers, limited access to information, and language difficulties faced by non-citizen consumers. These findings indicate a gap between universal legal norms and the implementation that remains biased toward citizenship status.The study concludes that although Indonesian regulations guarantee equality in consumer rights, there is a need to strengthen implementation mechanisms that are more inclusive, particularly for foreign consumers. This research contributes to the discourse on consumer protection by emphasizing the importance of harmonizing non-discrimination principles with the effectiveness of law enforcement.